2010
DOI: 10.1007/s10620-010-1416-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Prognostic Significance of CD151, c-Met, and Integrin alpha3/alpha6 in Pancreatic Ductal Adenocarcinoma

Abstract: CD151, c-Met, and integrin alpha3/alpha6 were all overexpressed in PDAC. CD151 and c-Met might be new molecular markers to predict the prognosis of PDAC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
68
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 44 publications
8
68
0
Order By: Relevance
“…Conversely, its abnormal stimulation, through overexpression (with or without gene amplification or mutations) or aberrant autocrine or paracrine HGF ligand production, mediates the activation of a wide range of different cellular signaling pathways involved in proliferation, scattering, and invasion (38). Accordingly, c-Met has been shown to be upregulated in many solid tumors, including PDAC (39,40), in which its stimulation has been associated with poor prognosis and chemoresistance (38,41). Moreover, it has been shown that c-Met plays a key role in the cancer/ stroma interaction (10), and is a marker for pancreatic cancer stem cells, representing an optimal target to prevent the development of metastases (42).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, its abnormal stimulation, through overexpression (with or without gene amplification or mutations) or aberrant autocrine or paracrine HGF ligand production, mediates the activation of a wide range of different cellular signaling pathways involved in proliferation, scattering, and invasion (38). Accordingly, c-Met has been shown to be upregulated in many solid tumors, including PDAC (39,40), in which its stimulation has been associated with poor prognosis and chemoresistance (38,41). Moreover, it has been shown that c-Met plays a key role in the cancer/ stroma interaction (10), and is a marker for pancreatic cancer stem cells, representing an optimal target to prevent the development of metastases (42).…”
Section: Discussionmentioning
confidence: 99%
“…For ITGA3, it has been established that α3β1 integrin is involved in the maintenance of basement membrane integrity through adhesion to laminin 5 and plays an essential role in the invasiveness and metastatic potential of tumor cells (30)(31)(32). However, there are contradictory reports regarding the significance of ITGA3 expression in various types of cancers (33)(34)(35)(36). Considering the results demonstrated recently that GAL3ST3 is involved in tumor metastasis by regulating the ability of adhesion to selectins and expression of integrins, more evidence is needed to clarify the relationship among these molecules (25).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, high levels of CD151 are correlated with poor prognosis in a variety of tumours including epithelial malignancies such as carcinomas of the lung, 68 breast (invasive ductal carcinoma), 34,53,69 colon, 70 pancreas, 71 kidney, 10 prostate (PCa), 72 liver 73,74 and oesophagus (SCC), 75 as well as glioblastoma. 76 As in most cancers an elevated level of CD151 expression is associated positively with a high tumour grade (Table 1), the assumption that CD151 is involved in cancer progression is well grounded.…”
Section: Clinical Aspects Of Cd151 Expressionmentioning
confidence: 99%
“…Indeed, overexpression of CD151 at the primary site was found to correspond with the development of metastases, mostly in lymph nodes. 53,71,[73][74][75] Formation of secondary tumours in distant organs such as lungs and bone was also noted in clear cell renal carcinoma (RCC). 10 CD151 is implicated as a potential diagnostic marker in osteosarcoma and prostate cancer.…”
Section: Clinical Aspects Of Cd151 Expressionmentioning
confidence: 99%